A Filipino paternal nurturance scale - Rayco, Domingo R., Jr. (2008)
This indigenous study sought to empirically define the construct of paternal nurturance or ugaling pagkamapagkalinga ng ama from the viewpoint of Filipino Metro Manila-based late adolescents 16 to 19 years old - 513 of them provided the conceptual definition, resulting in the construction of the initial 182 items and 1,161 who provided data for the final instrument and its psychometric properties. The initial 182 items were factor analyzed, using 0.7 as item factor loading cut-off, resulting in a unidimensional scale in Filipino composed of 25 items.
Keywords: Nurturing behavior; Love, Paternal; Fatherhood; Fathers; Parenting